Evolution of the EKA family of powdery mildew avirulence-effector genes from the ORF 1 of a LINE retrotransposon. (December 2015) - Amselem, Joelle; Vigouroux, Marielle; Oberhaensli, Simone; Brown, James; Bindschedler, Laurence; Skamnioti, Pari; Wicker, Thomas; Spanu, Pietro; Quesneville, Hadi; Sacristán, Soledad
Abstract Background TheAvrk1 andAvra10 avirulence (AVR) genes encode effectors that increase the pathogenicity of the fungusBlumeria graminis f.sp.hordei (Bgh ), the powdery mildew pathogen, in susceptible barley plants. In resistant barley, MLK1 and MLA10 resistance proteins recognize the presence of AVRK1 and AVRA10, eliciting the hypersensitive response typical of gene for gene interactions.Avrk1 andAvra10 have more than 1350 homologues inBgh genome, forming theEKA (E ffectors homologous toAvr k 1 andAvr a 10) gene family. Results We tested the hypothesis that theEKA family originated from degenerate copies of Class I LINE retrotransposons by analysing theEKA family in the genome ofBgh isolate DH14 with bioinformatic tools specially developed for the analysis of Transposable Elements (TE) in genomes. The Class I LINE retrotransposon copies homologous toAvrk1 andAvra10 represent 6.5 % of theBgh annotated genome and, among them, we identified 293 AVR/effector candidate genes. We also experimentally identified peptides that indicated the translation of several predicted proteins fromEKA family members, which had higher relative abundance in haustoria than in hyphae. Conclusions Our analyses indicate thatAvrk1 andAvra10 have evolved from part of the ORF1 gene of Class I LINE retrotransposons. The co-option ofAvra10 andAvrk1 as effectors from truncated copies of retrotransposons explains the huge number of homologues inBgh genome that could act as dynamic reservoirs from which new effector genes may evolve. These data provide further evidence for recruitment of retrotransposons in the evolution of new biological functions.